(untitled) (Global Journal of Medical Research, 2013)
Objectives: This study dealt with characterization of maxillary sinus in patients with facial pain using ultrasound. Methods: It was carried out on 50 complaint patients of maxillary sinus problems who were referred to the National Center of Ear, Nose, and Throat. The instruments used were; Aloka SSD 500, Honda HS2000 portable with curvilinear probe 3.5MHz, and General ElectricLOGIQ5 Mobile with curvilinear and linear probe (3.5MHz, 10MHz). Results: patients were 27males (54%) and 23 females (46%), their ages ranging between (20-70 years) and the most affected age group was (20-30years). All of them were of maxillary pain (100%), 28 patients (56%) of halitosis, 29 (58%) postnasal drip, 30 (60%), stuffy nose, 27 (54%) fever and 17(34%) with of malaise. All patients were diagnosed previously by computerized tomography( CT )coronal scans, Ultrasounds findings in the maxillary sinuses of the patients were 30% polyps with hypo echoic cavity, 12% fluid with hypo echoic cavity with posterior margin was seen,2% cyst with hypo echoic area with well defined borders,12% mucosal thickening, 38% normal sonographic appearance of hyper echoic anterior wall and cavity and the posterior margins were not seen, 6% polyps mucosal thickening with hypo echoic cavity with echogenic bony walls. Conclusion: It concluded that the ultrasound has an sensitivity of76.6% and spasticity of 92.2% and ultrasound is beneficial in diagnosis of maxillary sinus pathology and could be used as one of the diagnostic imaging modality as it is easy, with no radiation hazards and non invasive.